The impact of organizational position level and cultural flow direction on the relationship between cultural intelligence and expatriate cross-border adaptation. Issue 2 (7th April 2021) - Zhang, Ying; Li, Yuran; Frost, Mark; Rong, Shiyu; Jiang, Rong; Cheng, Edwin T.C.
Abstract : Purpose: This paper aims to examine the critical role played by cultural flow in fostering successful expatriate cross-border transitions. Design/methodology/approach: The authors develop and test a model on the interplay among cultural intelligence, organizational position level, cultural flow direction and expatriate adaptation, using a data set of 387 expatriate on cross-border transitions along the Belt & Road area. Findings: The authors find that both organizational position level and cultural flow moderate the relationship between cultural intelligence and expatriate adaptation, whereby the relationship is contingent on the interaction of organizational position status and assignment directions between high power distance and low power distance host environments. Originality/value: Previous research has shown that higher levels of cultural intelligence are positively related to better expatriate adaptation. However, there is a lack of research on the effect of position difference and cultural flow on such relationship. Our study is among the first to examine how the interaction between cultural flow and organizational position level influences the cultural intelligence (CI) and cultural adjustment relationship in cross-cultural transitions.